ANTIMICROBIAL ACTIVITY OF METHANOL EXTRACT FROM STEM BARK OF Cinnamomum sintoc - Nurdin Saidi; Hira Helwati; Lailatul Qhadariah Lubis; Muhammad Bahi (Jurnal Natural, 2017)
Antimicrobial activity of methanol extract from stem bark of Cinnamomum sintoc has been evaluated against Candida albicans, Staphylococcus aureus and Escherichia coli. The extraction of compound was carried out by maceration, then isolation by column chromatograph, which yielded five (5) subfractions (A-E). Activity against fungus C. albicans, S. aureus bacteria dan E. coli using agar dilution method in paper disk. Methanol extract was not potent against antifungal activity but shows antibacterial activity with medium category. Subfraction C showed that antibacterial activity against S. aureus and E. coli with weak category, but subfractions D and E did not show any activity.